Human papillomavirus prevalence and distribution in self‐collected samples from female university students in Maputo. Issue 2 (25th March 2020) - Bule, Yara Priscilla; Silva, Jani; Carrilho, Carla; Campos, Carla; Sousa, Hugo; Tavares, Ana; Medeiros, Rui
Abstract: Objective: To characterize human papillomavirus (HPV) prevalence and distribution among female university students in Maputo, Mozambique, and evaluate the determinants of HPV infection. Methods: A cross‐sectional study among 504 female university students between February and April 2017. Cervicovaginal self‐collected samples were analyzed for HPV genotypes by polymerase chain reaction‐restriction fragment length polymorphism and Anyplex TM II HPV28 Detection kit (Seegene ® ). Results: The prevalence of any HPV genotype was 28.6% (144/504). Single and multiple HPV infections were detected in 76 (15.1%) and 68 (13.5%) participants, respectively. Prevalence of high‐risk HPV was significantly higher than that of low‐risk HPV ( P <0.001). HPV16 was the most frequent genotype, followed by HPV58, HPV66, HPV52, HPV18, HPV56, HPV61, and HPV70. The prevalence of genotypes covered by the bivalent, quadrivalent, and nonavalent vaccine was 14.3%, 15.9%, and 23.4%, respectively. Number of sexual partners over lifetime and in the past 12 months was associated with HPV infection ( P <0.001 and P =0.039, respectively). Conclusions: Knowledge of HPV genotype‐specific prevalence among young women is important to set up strategies for HPV vaccination. The findings suggest that introduction of the nonavalent HPV vaccine might be the way forward in the present low‐resource setting. In addition, self‐sampling was useful for HPV detection and genotyping. Abstract : In‐depth knowledge of HPV genotype‐specific prevalence among young women in Maputo (Mozambique) is important for HPV vaccination strategies.